Mapping of global research output in congenital cataracts from 1903 to 2021. Issue 48 (3rd December 2021) - Idriss, Lujain Talaat; Hussain, Maryam; Khan, Muhammad; Ahmad, Tauseef; Muhammad, Khushi; Baig, Mukhtiar; Khan, Muhammad Mumtaz; Inamullah,
Abstract : Supplemental Digital Content is available in the text Abstract: Background and aim: Globally, congenital cataract remains one of the main causes of visual loss in children. This study was designed to plot the overall research output and evaluate some key bibliometric indicators in congenital cataracts research. Methods: Publications on congenital cataracts were retrieved from the Web of Science Core Collection database. The published literature was searched using the keywords "congenital cataract" OR "congenital cataracts" in the title filed with document types and language restrictions. The data were exported into HistCite to analyze; publication year, top authors, countries, institutions, journals, keywords, and most cited studies. VOSviewer software was used to construct network visualization mapping. Results: A total of 1427 publications (1903–2021) published in English language were included in this study. Over the past few decades, the total number of publications in congenital cataracts was found to be increased. The most productive year was 2016 (n = 72), while the most cited year was 1941 (1268 citations). The Investigative Ophthalmology & Visual Science (Impact Factor: 4.799) was the most attractive journal with 161 publications, and the Molecular Vision (Impact Factor : 2.367) was the most cited journal with 1915 citations and 161.723 citations per year. The most productive country was the United States of America (USA) (n = 325), while the most active institute was Sun Yat-sen University, China (n = 36). The most prolific author was Yao K (n = 27). The most studied Web of Science category was ophthalmology (n = 852). The most widely used keyword was congenital (n = 1427). The most cited paper in congenital cataracts was "Congenital cataract following German measles in the mother, cited 1268 times. The USA and author keyword congenital cataract had the highest total link strength. Conclusion: These findings provide useful insights, current status, and trends in clinical research in congenital cataracts. This study can be used to identify future research areas and standard bibliography references for better diagnosis and disease control.